Ceramic collections from the citadel of the Uzundara fortress have been dated as the first third of the 3rd century BCE. (September 2022) - Dvurechenskaya, Nigora D.
Abstract: This paper presents preliminary archaeological data of the Uzundara fortress, one of the military settlements founded at the border between Bactria and Sogdina regions, in the context of the military campaigns of Alexander the Great and his successors in Central Asia. Recent archaeological and numismatic evidence reveal that a garrison of the Greek- Macedonian army was stationed at Uzundara (Long gorge) at the beginning of the 295–280 BCE during the kingdom of Seleucus I or Antiochus I in order to protect the border and the oasis of northern Bactria from the nomad invasions; the fortress remained encamped by the Greek-Bactrian kingdom until its final collapse in 150–130 BCE. The paper focuses on the archaeological contextualization and the typological evaluation of three ceramic collections found in several areas of Citadel of the Uzundara fortress, which have been accurately dated by numismatics to 295–261 BCE. These collections include several types of tableware, common use items, and storage jars whose shapes and surface finishing resemble those of the ancient pottery in Hellenistic tradition discovered at the nearby settlements.